2022
DOI: 10.1182/blood.2022016033
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic and phosphoproteomic landscapes of acute myeloid leukemia

Abstract: We have developed a deep-scale proteome and phosphoproteome database from 44 representative Acute Myeloid Leukemia (AML) patients from the LAML TCGA dataset, and 6 healthy bone marrow derived controls. After confirming data quality, we orthogonally validated several previously undescribed features of AML revealed by the proteomic data. We identified examples of post-transcriptionally regulated proteins both globally (i.e. in all AML samples), and also, in patients with recurrent AML driver mutations. For examp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 89 publications
2
24
0
Order By: Relevance
“…S1E). From these 92, five genes ( MRC1 , CD163 , FGR , GASK1B , and RASA3 ) could predict overall survival (OS) in at least two AML cohorts and were differentially expressed between the paired CD34 + or CD34 − compartments of patients with AML [except for MRC1 , mainly due to monocytic blasts ( 20 )] (fig. S1F).…”
Section: Resultsmentioning
confidence: 99%
“…S1E). From these 92, five genes ( MRC1 , CD163 , FGR , GASK1B , and RASA3 ) could predict overall survival (OS) in at least two AML cohorts and were differentially expressed between the paired CD34 + or CD34 − compartments of patients with AML [except for MRC1 , mainly due to monocytic blasts ( 20 )] (fig. S1F).…”
Section: Resultsmentioning
confidence: 99%
“…A few studies have performed global proteomics and phosphoproteomics on AML patient material (e.g., [9][10][11][12][13][14][15][16][17]). The studies carried out thus far mainly served to identify diagnostic or prognostic markers, or to investigate the efficacy of novel treatments.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the decrease of BACH1 protein under cycloheximide (CHX) treatment was dramatically blocked in FBXO22 knockout THP-1 cells (F i g. 5 I). Furthermore, we analyzed the correlation between FBXO22 and BACH1 protein expression in the proteomic database of AML (PXD032110) [ 39 ]. The results showed that the protein expression of FBXO22 was negatively correlated with BACH1 protein level in primary AML patients, and patients with higher FBXO22 protein expression had lower BACH1 protein expression and vice versa (Fig.…”
Section: Resultsmentioning
confidence: 99%